The Psychological Dynamics of Future Hope for Children of Indonesian Migrant Workers in Kuala Lumpur, Malaysia - Sanjaya, Frisca Aulia Permata; Setiyowati, Ninik (Universitas Negeri Padang, 2025)
Malaysia is the main destination country for Indonesian Migrant Workers (PMI), with around 450,000 PMI recorded in 2024. Many migrant workers bring their children to live in the destination country. Although Law No. 6 of 2012 has regulated the rights of migrant workers' children, in reality many children have difficulty accessing education and health services due to limited information. This study aims to explore the psychological dynamics of children of Indonesian migrant workers in Malaysia. This study uses a qualitative phenomenology design approach. This study involved three informants of migrant worker children aged 12-18 years who live with their parents in Malaysia. Data collection was carried out through in-depth interviews, observations, and documentation. Data were analyzed using thematic analysis methods. The results of the study show that migrant workers' children face various challenges in achieving their future, thus forming the development of psychological dynamics. The psychological dynamics of future hopes for migrant workers' children are not formed singly, but through a complex process and mutual influence or reciprocity between personal, environmental and behavior taken. This research is expected to provide deeper insight into the psychological conditions of migrant workers' children, as well as provide policy recommendations to support their welfare, especially in terms of education and access to other basic services.